PENGARUH PROMOSI KESEHATAN REPRODUKSI TERHADAP PENGETAHUAN DAN SIKAP TENTANG SEKS PRANIKAH PADA REMAJA - Maximilianus Dasril Samura; Martha Sitorus (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2018)
Knowledge and attitude is a psychological factor that plays an important to role influence someone behavior. Teenagers premarital sex is very important notice nowadays, because in the last few decades this premarital sex become an important health issue not only among teenegers but it also occur in large number of developed and developing countries. The purpose of this research was to determine the knowledge and attitudes of teenagers about teenagers premarital sex at SMP Negeri 02 Satu Atap Kecamatan Patumbak. This research used pre experiment method, where as the data collecting is done by interview with the tool of questioner, this research method used one grup pre-test post-test design. The population of this research were all of the second grade students of junior high school as many as 153 peoples and sampling used was probability sampling, with simple random sampling technique counted 96 peoples. Statistic test used T paired sample t-test with computerization and test result as follows: (1) knowledge before and after counseling (p = 0.000), (2) attitude before and attitude after counseling (p = 0.000). Suggestions from research that for the school is expected to understand and realize the intellectual ability of learners and developed for the potential of each individual materialized in accordance with their respective differences, especially regarding reproductive health in order to prevent teenagers premarital sex